Assessment of aggregate index of systemic inflammation and systemic inflammatory response index in dry age-related macular degeneration: a retrospective study - Sannan, Naif S. (Frontiers in Medicine, 2023)
Inflammation is known to contribute to the development of age-related macular degeneration (AMD). Several inflammatory indices derived from routine complete blood counts have been proposed as biomarkers in multiple disorders. In this study, Clinical and laboratory data were retrospectively collected from medical records to assess the aggregate index of systemic inflammation (AISI) and the systemic inflammatory response index (SIRI) as potential biomarkers of systemic inflammation in patients with early diagnosis of dry AMD. The study included 90 patients with dry AMD and 270 age/sex-matched patients with cataracts as a control group. There were no significant differences in the AISI and SIRI results between the cases and controls (P=0.16 and 0.19, respectively). This suggests that AISI and SIRI may be inadequate metrics for AMD or lack sensitivity in detecting inflammatory changes. Exploring other routine blood markers may help to identify and prevent the early stages of AMD.